Dickkopf-related protein 1 and gremlin 1 show different response than frizzled-related protein in human synovial fluid following knee injury and in patients with osteoarthritis. Issue 6 (June 2018) - Huang, X.; Post, J.N.; Zhong, L.; Leijten, J.; Larsson, S.; Karperien, M.; Struglics, A.
Summary: Objective: To explore the involvement of the wingless-type MMTV integration site (WNT) and bone morphogenetic protein (BMP) antagonists dickkopf-related protein 1 (DKK1), frizzled-related protein (FRZB) and gremlin 1 (GREM1) in knee injury and osteoarthritis (OA). Design: The antagonists were immunoassayed in synovial fluid from a cross-sectional cohort of nine knee healthy reference subjects, patients with recent (0–77 days, n = 158) or old (1–37 years, n = 50) knee injuries, and OA ( n = 22). Cartilage (ARGS-aggrecan, cartilage oligomeric matrix protein and C2C type II collagen) and other biomarkers were assessed in synovial fluid in a subset of samples. Statistical analysis was by Kendall's tau ( τ ) correlation, Mann–Whitney U test, and linear regression analysis. Results: Compared to references, median concentration of GREM1 (but not DKK1 and FRZB) was elevated 1.5-fold immediately after injury, and FRZB was reduced 1000-folds in OA. All three antagonists decreased with increasing time after injury as well as with increasing age, but the temporal change after injury was less accentuated for FRZB (peaked 8–22 days after injury) compared to that of DKK1 and GREM1 (peaked immediately after injury). In the recent injury group, there was a correlation between GREM1 and DKK1 ( τ = 0.172); FRZB concentrations correlated with concentrations of cartilage biomarkers ( τ between 0.257 and 0.369), while DKK1 and GREM1 were inversely correlated ( τ between −0.177 and −0.217) with these markers. Conclusions: Our results indicate separate roles for the antagonists, where DKK1 and GREM1 had similarities in response to injury and in OA, with a different response for FRZB.